2022
DOI: 10.1021/acs.jmedchem.2c00401
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring In Vivo Performances of Protein–Drug Conjugates Using Site-Selective Dual Radiolabeling and Ex Vivo Digital Imaging

Abstract: In preclinical models, the development and optimization of protein–drug conjugates require accurate determination of the plasma and tissue profiles of both the protein and its conjugated drug. To this aim, we developed a bioanalytical strategy based on dual radiolabeling and ex vivo digital imaging. By combining enzymatic and chemical reactions, we obtained homogeneous dual-labeled anti-MMP-14 Fabs (antigen-binding fragments) conjugated to monomethyl auristatin E where the protein scaffold was labeled with car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…monitor the in vivo fate of an ADC (Figure 5) which was dual-labeled with 3 H and 14 C (Cahuzac et al, 2022).These studies confirmed the feasibility of dual radiolabeling for pharmacokinetic study of ADCs. Moreover, liquid scintillation counter (LSC) is a radioactivity meter that uses a liquid scintillator to accept radiation and convert it into fluorescent photons.…”
Section: Cahuzac Et Al Used Dual Radiolabeling and Ex Vivo Digital Im...supporting
confidence: 56%
“…monitor the in vivo fate of an ADC (Figure 5) which was dual-labeled with 3 H and 14 C (Cahuzac et al, 2022).These studies confirmed the feasibility of dual radiolabeling for pharmacokinetic study of ADCs. Moreover, liquid scintillation counter (LSC) is a radioactivity meter that uses a liquid scintillator to accept radiation and convert it into fluorescent photons.…”
Section: Cahuzac Et Al Used Dual Radiolabeling and Ex Vivo Digital Im...supporting
confidence: 56%
“…Conversion of the Bud-RG intermediates to full linkers was achieved convergently by the direct reaction of these HCl salts with p -nitrocarbonates represented by 20 in the presence of N , N -diisopropylethylamine (DIPEA) (Scheme ). , We chose to terminate our linkers in a standard maleimide–caproamide (MC) conjugation group for screening purposes. This conjugation motif is prevalent in the ADC field, featuring prominently across FDA-approved ADC therapies, thereby providing a useful benchmark.…”
Section: Resultsmentioning
confidence: 99%
“…Standard methods for evaluating the pharmacokinetic and tissue distribution profiles of a drug candidate involve tissue harvesting, homogenization, and quantification using liquid chromatography/tandem mass spectrometry (LC-MS/MS). While those methods will still be necessary for full characterization of a lead compound, direct radiolabeling provides a unique way to visually assess and quantify the whole-body distribution of multiple drug candidates early in their development and has mainly been used in preclinical evaluation of antibody-drug conjugates (ADCs) and nanoparticles. Here, we used the MMC scaffold to directly label MMC­(TMZ)-TOC and (i) determined the amount of conjugate that reached the tumor and (ii) quantified biodistribution in nontumor tissues in vivo using noninvasive nuclear imaging (PET/CT scan) and ex vivo γ counting. We observed a favorable biodistribution profile for the PDC that was similar to that of 68 Ga-DOTA-TOC: high tumor uptake, rapid kidney clearance, and low accumulation in normal tissues (Figure ).…”
Section: Discussionmentioning
confidence: 99%